The Throne of Fire - Riordan, Rick (London Puffin Books, 2012)
Carter Kane and his sister must prevent the chaos snake Apophis from breaking free or the world will come to an end. To have any chance of battling these Forces of Chaos, the Kanes must revive the sun god Ra.
Keywords: Brothers and sisters -- Mythology, Egyptian -- Magic